Inhibitory effect of microplastics on soil extracellular enzymatic activities by changing soil properties and direct adsorption: An investigation at the aggregate-fraction level. (December 2020) - Yu, Hong; Fan, Ping; Hou, Junhua; Dang, Qiuling; Cui, Dongyu; Xi, Beidou; Tan, Wenbing
Abstract: Microplastics (MPs), as a new type of environmental pollutant, pose a serious threat to soil ecosystems. The activities of soil extracellular enzymes produced by microorganisms are the potential sensitive indicators of soil quality. However, little is known about the response mechanism of enzyme activities toward MPs on a long-term scale. Moreover, information on differences in enzyme activities across different soil aggregates is lacking. In this study, 150 days of incubation experiments and soil aggregate fractionation were combined to investigate the influence of MPs on extracellular enzyme activities in soil. 28% concentration of polyethylene with size 100 μm was adopted in the treatments added with MPs. The results show that MPs inhibited enzyme activities through changing soil nutritional substrates and physicochemical properties or through adsorption. Moreover, MPs competed with soil microorganisms for physicochemical niches to reduce microbial activity and eventually, extracellular enzyme activity. Enzyme activities in different aggregate-size fractions responded differently to the MPs exposure. The catalase in the coarse particulate fraction and phenol oxidase and β-glucosidase in the micro-aggregate fraction exerted the greatest response. With comparison, urease, manganese peroxidase, and laccase activities showed the greatest responses in the non-aggregated silt and clay fraction. These observations are believed to stem from differences in the key factors determining the enzyme activities in different aggregate-size fractions. The inhibitory pathway of microplastics on activities of extracellular enzymes in soil varies significantly across different aggregate fractions. Graphical abstract: Image 1 Highlights: Microplastics (MPs) significantly inhibited extracellular enzyme activities in soil. MPs affected enzyme activities through adsorption and altering microenvironment. Effect of MPs on enzyme activities varied across different soil aggregate levels. DOC and OP were significant factors shaping enzyme activities in the presence of MPs. Enzyme activities was more sensitive to MPs in the smaller soil aggregate fraction.